A dimensão ambiental da educação: os conteúdos ambientais em escolas públicas das comunidades carentes - Fonseca, Valter Machado da (2007)
This dissert is linked to the Programa de Mestrado of the Faculdade de Educação da Universidade Federal de Uberlândia MG (FACED/UFU) s research line Knowing and Educative Practices. Its central question is to verify how the docents practices act with the environmental contents of the public schools in the city s poor periphery. To realize this analysis, has been chosen a public school located on a poverty area of the Uberaba (MG) city s periphery. To this work, has been elected the disciplines of Geography, Biology and Chemistry, exactly for the proximity of these disciplines and the researched object. To the inquiry, was chosen only one 1st Year class of the Medium Level. The used methodology was: direct observation in classroom, application of questionnaires to the students and inhabitants of the community situated in the school s area and interviews with the three teachers of the mentioned disciplines. The theoretical/conceptual fundaments of this works are launched to the utilization of the historic materialism, objectifying to comprehend the urban ambient and its problems, from the analysis of this environment under the optic of the social inequalities and the social/space segregation, decurrent of the current model of economic production: the capitalist society. For this was preponderant a study of the relations capital/work, the process of industrialization/urbanization and the concepts that comes from the relation society/nature, taking in consideration the development of the current model of production, as the relation school/education with this model, considering the environmental aspect while a dimension of the education. The used theoretical line was based in authors as Karl Marx, Ístvan Mészáros, Antonio Gramsci, Ricardo Antunes, David Harvey, Paulo Freire, Bernard Charlot, Enrique Leff, Henri Lefebvre, Carlos Frederico B. Loureiro, Carlos Walter Porto Gonçalves, Genebaldo Freire Dias, Edgar Morin, Félix Guattari, and many others thinkers. The research has detected important data like the imbalance between the teaching practices involving the environmental contents and the notion of the thematic primary concepts, the existence of a satisfactory rating of environmental perception involving the investigated community students, teachers and inhabitants, beyond a series of problems of the docent practices with these disciplines, between other factors. Finally, has been verified the necessity and possibilities of the work with the environmental contents, by intermediation of the dialogic relation between the school and the community, pointing to the challenge of the school to fulfill its social function and to assist the minimization of the urban environmental problems.